Human umbilical cord-derived mesenchymal stem cells utilise Activin-A to suppress Interferon-gamma production by natural killer cells. - Debanjana eChaterjee; Nicole eMarquardt; Dejene Milkessa Tufa; Tim eHatlapatka; Ralf eHass; Cornelia eKasper; Constantin evon Kaisenberg; Reinhold Ernst Schmidt; Roland eJacobs (Frontiers in Immunology, 2014)
Following allogeneic hematopoietic stem cell transplantation (HSCT), interferon (IFN)-gamma levels in the recipient’s body can strongly influence the clinical outcome. Human umbilical cord-derived mesenchymal stem cells (UC-MSCs) are lucrative as biological tolerance-inducers in HSCT settings. Hence, we studied the molecular mechanism of how UC-MSCs influence natural killer (NK) cell-mediated IFN-gamma production. Allogeneic NK cells were cultured in direct contact with UC-MSCs or cell free supernatants from MSC cultures (MSC conditioned media). We found that soluble factors secreted by UC-MSCs strongly suppressed IL-12/IL-18-induced IFN-gamma production by NK cells by reducing phosphorylation of STAT4, NF-kB as well as T-bet activity. UC-MSCs secreted considerable amounts of Activin-A, which could suppress IFN-gamma production by NK cells. Neutralisation of Activin-A in MSC-conditioned media significantly abrogated their suppressive abilities. Till date, multiple groups have reported that prostaglandin (PG)-E2 produced by MSCs can suppress NK cell functions. Indeed, we found that inhibition of PGE2 production by MSCs could also significantly restore IFN-gamma production. However, the effects of Activin-A and PGE2 were not cumulative. To the best of our knowledge, we are first to report the role of Activin-A in MSC-mediated suppression of IFN-gamma production by NK cells.